Transformational Leadership of the Provincial Administrative Organization President for Sustainable Local Development - Rattanabhibal, Narumol; Tokeaw, Wittayatorn; Sridee, Supaporn (Hatyai Academic Journal, 2024)
The Provincial Administrative Organization (PAO) is a form of local government. The president of the provincial administrative organization is the highest executive directly elected by the people. According to the Provincial Administrative Organization Act of 1997, provincial administrative organization presidents have powers as well as duties, and they serve as the highest authority commanding both city officials and regular government officials. They also have full responsibility for developing the province, which differs from other forms of government organization. In addition, changes in global society have resulted in the emergence of the concept of sustainable development as a guideline for achieving local or national development goals. When there are changes in politics, economy, and society, leaders need to change as well. They must develop themselves to have transformational leadership characteristics, including creating charisma or having influence with an ideology, inspiration, intellectual stimulation, consideration of individuality, giving rewards beyond expectations, management by omission, situational rewards, having confidence in followers, foresight, and accepting change. The important qualities of change leaders for sustainability include having a proactive and strong team, solving complex problems, thinking outside the box, creating innovations, possessing emotional stability, and viewing followers as human beings to make management both within and outside the organization successful. This will affect local development to be sustainable.